PENGARUH BRAND ENDORSER JKT48 TERHADAP KEPUTUSAN PEMBELIAN HONDA BEAT PADA PT.BINTANG KHARISMA JAYA DI BANDAR LAMPUNG - Saputra, Deli; Rafiq, Muhammad (Jurnal Manajemen Magister Darmajaya, 2015)
The rapid developing eraÂ  made the competition level at industry world. It forced the producers to do convinient marketing strategies to reach company goal and high product sale in market share. This aim of this study used was to measure how big the effct of brand endoser on purchase decision of Honda Beat motorcyle at PT. BintangÂ  Kharisma in Bandar Lampung. The method used was quantitative. The number of sampe was 100 respondents. The sample taking used was non probability sampling through purposive sampling techniques. The data collecting technique used was questionnaire. The data analysis technique used was simple linear regression. The research result showed that Brand Endorser significantly influenced Purchase Decision of Honda Beat at PT. Bintang Kharisma Jaya in Bandar LampungKeywords: Brand Endorser and Purchase Decision.